Parametric Evaluation of Digestability of Organic Fraction of Municipal Solid Waste for Biogas Production - Monoj Kumar Mondal; Aparna Banerjee (Journal of Sustainable Development of Energy, Water and Environment Systems, 2015)

(untitled)
Municipal solid waste was collected from Varanasi’s municipal solid waste dumpsite and sorted for organic fraction present in it. Current work showed the consequences of calcium hydroxide or lime digestion on organic fraction of municipal solid waste of Varanasi, India. The organic fraction of municipal solid waste sample was digested with desired amount of calcium hydroxide. The different concentrations (0.1, 0.2, and 0.5 %) of calcium hydroxide was blended separately to substrates (10 % total solid) at 30-35 ºC in 3 different beakers denoted by A1, A2 and A3, respectively of 2 L capacity. Experiments of hydrolysis step were conducted on all three samples for evaluation of chemical oxygen demand, pH and volatile fatty acids content in sample. The parameters measured during experiments were chemical oxygen demand, biogas production, total solid, volatile solids, total Kjeldahl nitrogen and total organic carbon. Rate enhancement of anaerobic digestion and biogas production were occurred for calcium hydroxide digested samples. Therefore calcium hydroxide can be used as an effective alkali for the digestion of organic fraction of municipal solid waste.